Automasi Pembuatan Laporan Analisis dengan R Markdown - Muhammad Yoga Prabowo; Amin Firdaus; Diding Ariadi Damanik; Taufan Dedy Nurtanto (Program Studi Ilmu Pemerintahan Universitas Muhammadiyah Buton, 2022)
A report is a form of official document that is often made by civil servants. Writing reports manually often takes time, energy, and other resources that can be utilized for other activities. In addition, manual report generation is prone to errors. Automation of report generation can provide a solution. The automation aims to make report generation faster, easier, and reduce the human error factor. Furthermore, the application of IT in automation of report generation is an implementation of good governance to increase efficiency and effectiveness. Automation can be done using the R Markdown function in the R statistical programming software. R Markdown can combine narrative, analysis, and visualization into a complete report. Loops and logical statements can also be used to generate automatic descriptions. The adoption of R Markdown for automation makes the composition of analytical reports more effective, efficient, and reproducible.